ANALISIS PENGGUNAAN FAKTOR PRODUKSI PADA PERUSAHAAN AYAM RAS PETELUR (STUDI KASUS PADA UD. KAKASKASEN INDAH DAN CV. NAWANUA FARM) - Salale, Chintia C.L; Rorimpandey, Boyke; Massie, Masje T; Waleleng, Poulla O.V (Universitas Sam Ratulangi, 2014)
ABSTRACT ANALYSIS OF PRODUCTION FACTOR UTILIZATION AT LAYING HEN FARMS (CASE STUDIES AT UD. KAKASKASEN INDAH AND CV. NAWANUA FARM). Laying hen farm can support the government program due to its prominence in egg productivity. The problem that must be evaluated were how much the profit in one period of production gained and how many the scale of laying hen farm to reach the break event point. The laying hen farms used in this study were UD. Kakaskasen Indah and CV. Kawanua Farm. The objectives of this study were to evaluate utilization of production factor, profit level and break event point. Research was conducted by survey method. Data were collected based on field observation and direct discussion with the owners of laying hen farms. Results showed that both laying hen farms had the largest production costs of 69.44% for animal feeding on CV. Kawanua Farm and 76.66% for animal feeding on UD. Kakaskasen Indah. Analysis of profit level on CV. Kawanua Farm were Rp. 5,247,257,316 per production period with farm scale of 21,000 heads of animals per production period. The BEP were Rp. 209,297,896 for 10,956 heads of animals, with MOS of 94.36% and ROI of 1.78. Analysis of profit level on UD. Kakaskasen Indah were Rp. 17,523,288,446 per production period with farm scale of 60,000 heads of animals per production period. The BEP were Rp. 517,417,088 for 24,851 heads of animals, with MOS of 96.38% and ROI of 1.25. Results of analysis showed that both laying hen farms were using the capital efficiently as indicated by profitable values of MOS and ROI above the break event point.Â Key Words : Production factor, BEP, MOS, ROI Â